DETERMINAN EARNING MANAGEMENT DAN PENGARUHNYA TERHADAP NILAI PERUSAHAAN (Studi Empiris Pada Perusahaan Manufaktur yang terdaftar di BEI Periode 2017-2018) - Derwin Juan Sagrim; Syaikhul Falah; Bill J.C Pangayow (JURNAL AKUNTANSI DAN KEUANGAN DAERAH, 2019)
This research has aim to examine the influence of investment opportunities set, board independence, and free cash flow toward firm value with earning management as the intervening variable in manufacturing companies listed on Indonesian Stock Exchange for period 2017 to 2018. This study used a sample of 43 companies with 6 years’ time period. The method of analysis is multiple regression model with further done with path analysis using SPSS 23. These results indicate that investment opportunities set and free cash flow have a significant direct effect on the value of the firm, while investment opportunity set and board independence have the indirect effect. Investment opportunities set, board independence, free cash flow and earning management simultaneously affect the firm value with adjusted R- squared 55.3%. Overall this study indicates that earning management has important role as the intervening variable betweeninvestment opportunities set, board independence & free cash flow relating to firm value.